2019
DOI: 10.1177/2470547019897030
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Hippocampus ERK2 Signaling Mediates Anxiolytic-Related Behavior in Male Rats

Abstract: Background: Anxiety disorders are the most common neuropathologies worldwide, but the precise neuronal mechanisms that underlie these disorders remain unknown. The hippocampus plays a role in mediating anxiety-related responses, which can be modeled in rodents using behavioral assays, such as the elevated plus maze. Yet, the molecular markers that underlie affect-related behavior on the elevated plus maze are not well understood. Methods: We used herpes simplex virus vector delivery to overexpress extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…However, six days post-SNL, anxiety- and depression-like behaviors were not completely developed even if SNL-induced aversion was detected ( Suzuki et al, 2007 ; Wu et al, 2019 ). However, the evidence demonstrated that the analyzed anxiety- and depression-related DEGs such as Gria1 ( Rivera et al, 2020 ), Mapk1 ( Sierra-Fonseca et al, 2019 ), Mapk9 ( Thomson et al, 2020 ), and Fkbp5 ( Zannas et al, 2019 ) contributed to anxiety or depression symptoms in rodents. The further study on the gene expression profiles and emotion-related behaviors including anxiety- and depression-like behaviors at the later stage of neuropathic pain should be carried out.…”
Section: Discussionmentioning
confidence: 97%
“…However, six days post-SNL, anxiety- and depression-like behaviors were not completely developed even if SNL-induced aversion was detected ( Suzuki et al, 2007 ; Wu et al, 2019 ). However, the evidence demonstrated that the analyzed anxiety- and depression-related DEGs such as Gria1 ( Rivera et al, 2020 ), Mapk1 ( Sierra-Fonseca et al, 2019 ), Mapk9 ( Thomson et al, 2020 ), and Fkbp5 ( Zannas et al, 2019 ) contributed to anxiety or depression symptoms in rodents. The further study on the gene expression profiles and emotion-related behaviors including anxiety- and depression-like behaviors at the later stage of neuropathic pain should be carried out.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that the various hippocampal regions subserve distinct functions, with the dorsal hippocampus involved in memory, learning and spatial learning, while the ventral hippocampus cooperates with the amygdala to regulate anxiety-related behavior 28 30 . More recently, it was shown that the dorsal CA1 subregion of the hippocampus is activated by an anxiogenic environment 31 and that genetic manipulation of the dorsal hippocampus has an anxiogenic effect 32 , 33 . Thus, the dorsal hippocampus plays a critical role in the regulation of anxiety behavior.…”
Section: Discussionmentioning
confidence: 99%
“…5 B, 6 B); highlighting a long-term FLX-induced molecular signature between the sexes that results in anxiety-like behavior in both females and males. Subsequently, we also evaluated intracellular hippocampal and prefrontal cortex ERK-CREB-BDNF signaling markers, given that these downstream molecules also modulate affect-related behavior in intact adult rodents 25 , 30 , 48 . Here, we found that juvenile FLX pretreatment resulted in a long-term decrease in the phosphorylation of ERK2 and CREB within both brain regions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is a classic task used to evaluate anxiety-like behavior in rodents 25 , 37 , 79 . Briefly, the animals were tested in a plus-shaped maze (under red light conditions; ~ 30 lx) that was elevated 50 cm from the floor.…”
Section: Methodsmentioning
confidence: 99%